CURRENT APPROACHES TOX-RAY METHODS OF DIAGNOSTICS IN PLANNING OF DENTAL IMPLANTS AND STAGES OF SURGICAL REHABILITATION OF PATIENTS WITH A SECONDARY EDENTIA - H.B. Prots; V.P. Puryk; Y.I. Solodzhuk; G.P. Nychyporuk; I.G. Omelchuk; Y.V. Puryk; A.K. Shudjairi; S.A. Ohiyenko; I.I. Prots (Український стоматологічний альманах, 2018)
Abstract. Inflammatory and degenerative processes in periodontal tissues in 80% of cases involve loss of teeth. The basic method of orthopedic treatment of patients with chronic forms of generalized periodontitis (GP), which is usually accompanied by loss of teeth, is prosthetic dental bridges [3,4,8].